Perancangan Urban Farming Mengatasi Global Warming Pada Bangunan Suzuya Kota Lhokseumawe - Rifa’i Berutu, Iqbal; Masthura Hassan, Soraya; Andriani, Dela (CV RIFAINSTITUT, 2024)
One of the most widely discussed global topics today is global warming and environmental degradation. Global warming refers to the increase in the earth's average temperature due to greenhouse gas emissions produced by human activities, while environmental degradation includes various forms of degradation of natural ecosystems due to pollution, deforestation, and other unsustainable practices. In fact, buildings play a significant role in both of these issues. The building planning process often involves the selection of materials that may not be environmentally friendly, as well as designs that are less efficient in energy use. During the construction phase, the use of heavy machinery and the transport of building materials generate considerable carbon emissions. In addition, the construction process often causes damage to land and natural habitats. Once the building is completed and starts operating, energy consumption for heating, cooling, lighting and other equipment continues, much of which relies on non-renewable energy sources and results in greenhouse gas emissions. In addition, the building also generates waste that needs to be properly managed to avoid further pollution. Thus, throughout their life cycle, from planning to operation, buildings contribute significantly to the problem of global warming and environmental damage, and therefore, a more sustainable approach in architecture and construction is needed to reduce these negative impacts.